The Control System and External Control of Organization - Willson Gustiawan (Jurnal Ilmiah Poli Bisnis, 2021)
This paper aims to discuss control - a function in an organization – by relooking some works in control system and external control of the organization. A classical work of Pfeffer and Salancik (1978) becomes an important basic source in this review paper discussing the external control of the organization from a resource dependence perspective. Luckily, Dill (1981) reviewed this ten chapters book giving a basic understanding of the control function of the organization. Dill also offered a term of the environment of an organization, the one that might be understood before understanding about the organization. Another important source comes from Eilon’s (1996) work which provides a theoretical framework on the basic concept of identifying and classifying of the administration control system. The more recent works in the control system strengthen this review paper such as Chenhall (2003) that provides a critical review of findings from contingency-based studies relating to the management control system (MCS), and Gillan (2006) describing corporate governance as another aspect in control function of management. This paper ends with concluded recommendations to answer the curiosity in understanding the organization and its environment and the external control of the organization. Makalah ini bertujuan untuk mendiskusikan pengendalian atau control - suatu fungsi dalam organisasi – dengan melihat kembali beberapa karya tulis dalam sistem pengendalian dan pengendalian eksternal organisasi. Karya Pfeffer dan Salanic (1978) menjadi bahan yang penting dalam makalah ini yang mendiskusikan pengendalian eksternal suatu organisasi dengan perspektif keterikatan sumber daya. Beruntung, bahwa Dill (1981) membahas buku yang terdiri atas sepuluh bab ini dan memberikan pemahaman mendasar mengenai fungsi pengendalian dalam organisasi. Dill juga memperkenalkan istilah lingkungan organisasi, sesuatu yang perlu dipahami terlebih dahulu sebelum membahas lebih lanjut tentang organisasi. Sumber bahan penting lain berasal dari karya Eilon (1996) yang memberikan kerangka teoretis sebagai konsep dasar dalam mengidentifikasi dan mengklasifikasikan sistem pengendalian administrasi. Karya lebih baru yang digunakan dalam makalah ini adalah Chenhall (2003) yang memberikan pandangan kritis dari temuan studi contingency based dalam sistem pengendalian manajemen (MCS), dan Gillan (2006) yang menjelaskan tentang corporate governance sebagai aspek lain dalam fungsi pengendalian manajemen. Makalah ini diakhiri dengan rekomendasi yang memberikan jawaban atas pemahaman tentang organisasi dan lingkungannya serta pengendalian eksternal organisasi.